2018
DOI: 10.2147/cmar.s182254
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer laterality and molecular subtype likely share a common risk factor

Abstract: BackgroundTo investigate the epidemiological features of breast cancer laterality and molecular subtypes in southern China.Materials and methodsA total of 2,049 cases who were diagnosed with unilateral breast cancer in the past 5 years were classified based on laterality and molecular subtypes. Molecular subtypes were defined in accordance with the 2013 St. Gallen recommendations.ResultsBreast cancer was more likely to be diagnosed in the left breast than in the right at a rate of around 5%. In the case of inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
3
10
1
Order By: Relevance
“…Notably, breast cancer in female is more likely to occur in the left breast than in the right (19). This finding has gained the attention of many researchers and numerous hypotheses have been proposed to account for the left-side dominance of breast cancer, but none have been uniformly accepted or confirmed (20,21). In this study, we found that left-side dominance was also a risk factor for pT1-2N0M0 TNBC, which has not been reported previously.…”
Section: Discussionsupporting
confidence: 50%
“…Notably, breast cancer in female is more likely to occur in the left breast than in the right (19). This finding has gained the attention of many researchers and numerous hypotheses have been proposed to account for the left-side dominance of breast cancer, but none have been uniformly accepted or confirmed (20,21). In this study, we found that left-side dominance was also a risk factor for pT1-2N0M0 TNBC, which has not been reported previously.…”
Section: Discussionsupporting
confidence: 50%
“…11 Cheng et al in 2018 observed that left sided breast cancer was approximately 5% more than the right breast. 12 Uyisenga et al in 2020 observed bilateral breast cancer in some patients. 13 Majority of the cases of breast carcinoma in our study had upper outer quadrant (55.7%) involvement followed by central (18.1%) cases, lower inner quadrant (14.9%), lower outer quadrant (8.6%) and upper inner quadrant (2.7%).…”
Section: Discussionmentioning
confidence: 96%
“… Not Applicable Left-side breast has slightly larger size Roychoudhuri R et al, 200 6[ 4 ]. Breast laterality ratio is 1.07 Not Applicable - Higher tissue mass in left-side breast which leads to increased cancer incidence Cheng SA et al, 201 8[ 5 ]. Laterality ratio in age < 40 years is 0.80 and in age > 40 years is 1.06 -Invasive carcinomas commonly affect the right-side breast at younger ages (< 40 years old).…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that right-handed patients examine their left-side breast and axilla more accurately than their right-side breast and axilla. This leads to an earlier discovery of smaller breast lesions in their left-side breast compared to the right-side breast [ 1 , 2 , 5 ]. It was also suggested that this might be the result of a stronger cell-mediated immune activity in the left-side of the human body [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation